Neurofibroma presenting as clitoromegaly - Dhande, Ashish; Chougle, Qurratulain Ali; Lal, Vikash; Gupta, Sumeet; Dhande, Kirtibala (International Journal of Research in Medical Sciences, 2017)
Congenital clitoromegaly is common, but acquired clitoromegaly due to neurofibroma is rare. Here we present a case report of Neurofibroma presenting as clitoromegaly. A 7 year female had history of painless clitoromegaly since 3 years. Her hormonal assays and radiological examination of abdomen and pelvis did not reveal any abnormality. She was subjected to clitoroplasty for correction of clitoromegaly.